Albert Schweitzer and Africa - Paget, James Carleton (Journal of religion in Africa, 2012)
Abstract This article re-examines the question of Albert Schweitzer's career as a medical missionary in the Gabon. After noting that Schweitzer has rarely been the subject of any discussion among Africanists and explaining why that is the case, the article looks at why Schweitzer decided to go to the Gabon, how he perceived his role there, how his attitudes to colonialism evolved, and what role his African experience played in the evolution of his thought. Among other things, the article seeks to bring out tensions and contradictions in Schweitzer's relationship to the African continent.